2013
DOI: 10.1002/acr.22010
|View full text |Cite
|
Sign up to set email alerts
|

Treating to a Target in Established Active Rheumatoid Arthritis Patients Receiving a Tumor Necrosis Factor Inhibitor: Results From a Real‐World Cluster‐Randomized Adalimumab Trial

Abstract: Objective. In early rheumatoid arthritis (RA), treating to a target is more effective than routine care (RC). Our aim was to determine if treating to a target has better outcomes than RC in established active RA. Methods. We used a real-world, 18-month cluster-randomized trial in established active RA patients treated with adalimumab. Physicians were randomized to RC, treating to a Disease Activity Score in 28 joints (DAS28) of <2.6 (DAS group), or treating to a 0 of 28 swollen joint count (SJC; 0-SJC group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 16 publications
0
77
0
Order By: Relevance
“…50,52,63 One cluster RCT was rated as being at high risk of bias for blinded outcome assessment, 63 whereas the other two cluster RCTs were rated as being at unclear risk for this domain. 50,52 All three cluster RCTs were rated as being at high risk of attrition bias (> 10% participants withdrawing). 50,52,63 A trial protocol was not available for two cluster RCTs that were rated as being at unclear risk of bias for selective reporting.…”
Section: Risk-of-bias Judgements For Included Non-cluster Randomised mentioning
confidence: 99%
See 4 more Smart Citations
“…50,52,63 One cluster RCT was rated as being at high risk of bias for blinded outcome assessment, 63 whereas the other two cluster RCTs were rated as being at unclear risk for this domain. 50,52 All three cluster RCTs were rated as being at high risk of attrition bias (> 10% participants withdrawing). 50,52,63 A trial protocol was not available for two cluster RCTs that were rated as being at unclear risk of bias for selective reporting.…”
Section: Risk-of-bias Judgements For Included Non-cluster Randomised mentioning
confidence: 99%
“…the TIght COntrol for RA (TICORA) trial 61 examined patients with a disease duration of < 5 years and van Hulst et al 63 reported including both newly diagnosed patients and those with established disease (and did not report on the findings for these patients separately at all)]. Six studies 50 52,53 the T-4 study 56,57 and the TEAR trial [58][59][60] ) and six studies 26- 54 and the TEAR trial [58][59][60] ). Two studies 9,35,36,67 made other comparisons which did not seem to fit with any of the above comparisons (i.e.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations